2019
DOI: 10.1002/ejhf.1379
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound integrated with clinical assessment for the diagnosis of acute decompensated heart failure in the emergency department: a randomized controlled trial

Abstract: AimsAlthough acute decompensated heart failure (ADHF) is a common cause of dyspnoea, its diagnosis still represents a challenge. Lung ultrasound (LUS) is an emerging point-of-care diagnostic tool, but its diagnostic performance for ADHF has not been evaluated in randomized studies. We evaluated, in patients with acute dyspnoea, accuracy and clinical usefulness of combining LUS with clinical assessment compared to the use of chest radiography (CXR) and N-terminal pro-B-type natriuretic peptide (NT-proBNP) in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
117
2
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(134 citation statements)
references
References 55 publications
4
117
2
11
Order By: Relevance
“…A scoring system, in which a minimum number of B‐lines in one intercostal space per zone is used to define a zone as ‘positive.’ Positive zones are then summed to delineate a cut‐off value. For example, ≄3 B‐lines in two zones on each hemithorax are consistent with a diagnosis of pulmonary oedema in dyspnoeic patients presenting to the emergency department …”
Section: Reporting Checklistmentioning
confidence: 93%
“…A scoring system, in which a minimum number of B‐lines in one intercostal space per zone is used to define a zone as ‘positive.’ Positive zones are then summed to delineate a cut‐off value. For example, ≄3 B‐lines in two zones on each hemithorax are consistent with a diagnosis of pulmonary oedema in dyspnoeic patients presenting to the emergency department …”
Section: Reporting Checklistmentioning
confidence: 93%
“…Combining lung ultrasound with clinical evaluation reduced diagnostic errors by 7.98 cases/100 patients, as compared to only 2.42 cases/100 patients in the chest X‐ray/NT‐proBNP group. This study shows the greater accuracy of lung ultrasound compared with the standard approach for the diagnosis of HF in the emergency department …”
Section: Imagingmentioning
confidence: 78%
“…Lung ultrasound plays a major role in the assessment of patients with acute and chronic HF . Pivetta et al . tested its usefulness for the diagnosis of HF in 518 patients with breathlessness in the emergency department in a prospective, randomized, study.…”
Section: Imagingmentioning
confidence: 99%
“…In this issue of the Journal, the study by Pivetta et al . is the first randomized controlled trial that examined the accuracy and clinical usefulness of a strategy that combines clinical assessment with LUS as compared to clinical assessment plus chest X‐ray (CXR) and NP testing for the diagnosis of AHF.…”
mentioning
confidence: 99%
“…Recently, shorter time‐to‐first administration of intravenous furosemide has been associated with improved in‐hospital survival of AHF patients . Since Pivetta et al . have shown that the integrated LUS strategy decreases time to confirmation of AHF diagnosis by approximately 95% as compared to integrated CXR/NP strategy, it may be hypothesized that the LUS strategy would facilitate earlier commencement of decongestive therapy and probably lead to better outcomes.…”
mentioning
confidence: 99%